(untitled) (Conferencea, 2023)
In the article, the concept of information technologies, their methods, ways of increasing its effectiveness, introduction of new information technologies in education. It is stated about the need to use them, to get positive results, to organize the educational process in accordance with the hygiene standards set for elementary classes, to provide basic knowledge about information technologies in the digital environment.